Life cycle environmental and economic sustainability of Stirling engine micro‐CHP systems. Issue 6 (18th May 2018) - Stamford, Laurence; Greening, Benjamin; Azapagic, Adisa
Abstract: Micro‐combined heat and power (micro‐CHP) systems have gained prominence in Europe and elsewhere, often attracting government incentives. Of the various micro‐CHP technologies, Stirling engine (SE) systems are often preferred over internal combustion engines, but their economic and environmental sustainability is unclear. This study uses life cycle assessment and life cycle costing to analyze SE micro‐CHP units, comparing the results to conventional natural gas boilers and grid electricity. Assuming highly‐efficient operation (77 % thermal; 13 % electrical efficiency), the SE system is preferable to conventional electricity and heat both economically and environmentally (for nine of 11 impacts). However, at more realistic efficiencies (71 % thermal; 6 % electrical), the SE system is uncompetitive, being worse for seven environmental impacts, including global warming, and incurring 9 % higher costs, despite subsidy. The choice of electricity, heat or combined output as a functional unit greatly affects the results. At low efficiencies, per unit of electricity, the SE system has on average 44 % worse environmental performance than grid electricity. However, per unit of heat it is, on average, 30 % better environmentally than the gas boiler, but the global warming potential (GWP) is 19 % worse. For combined energy output, the SE system has on average 3 % lower impacts than conventional alternatives, but the GWP is 16 % higher. Future improvements to the environmental impacts of the electricity grid mix, including its decarbonization, would further reduce any relative benefits of the SE system, calling into question the suitability of subsidy. Abstract : Stirling not so sterling? Micro‐combined heat and power (micro‐CHP) systems are gaining in prominence. Life cycle assessment and life cycle costing are used to analyze a Stirling engine (SE) micro‐CHP system, comparing it to natural gas boilers and grid electricity ("conventional" energy system). Micro‐CHP is found to be environmentally and economically beneficial at high efficiencies, but analysis based on real operational efficiencies shows it to be uncompetitive both environmentally and economically.